Study of Th1/Th2 balance in peripheral blood mononuclear cells of patients with alopecia areata - Sadeghi, Soha; Sanati, Mohammad Hossein; Taghizadeh, Morteza; Mansouri, Parvine; Jadali, Zohreh (Acta microbiologica et immunologica Hungarica, 2015)
Alopecia areata represents an autoimmune pathological process driven primarily by cellular aberrations contained within the immune system, which activates various humoral and cellular elements of the immune response. The aim of this study was to determine the mRNA expression levels of T-bet and GATA-3 as potential inducers of T helper (Th)1 and Th2 differentiation, respectively, as well as Th1(IFN-γ) and Th2(IL-4) cytokine mRNA expression in patients with alopecia areata. Using real-time reverse transcriptase PCR (RT-PCR), the relative amounts of T-bet, GATA-3, IFN-γ, and IL-4 mRNA transcripts were determined in PBMCs from 20 Iranian patients with alopecia areata and compared with those of 20 healthy control subjects. In comparison with the normal group, T-bet and IFN-γ mRNA expression levels were significantly up-regulated in the alopecia areata patients, while GATA-3 and IL-4 mRNA expression levels were down-regulated. Notably, positive correlation (P < 0.05) was found between IFN-γ and T-bet levels in patients and controls. In addition, significant positive correlations existed between GATA-3 and IL-4 (P < 0.05). These results indicate that a Th1/Th2 imbalance exists in alopecia areata, and it may be implicated in the pathogenesis of disease.